FUNCTIONAL ROLE OF METAPHORS IN COMPUTER GAMES (THE EXAMPLE OF «DEAR ESTHER», «BRAID», AND «ANTICHAMBER») - S. V. Borisova (Вестник Кемеровского государственного университета, 2013)
The paper analyzes the functional characteristic of metaphors. With the example of such games as «Dear Esther», «Braid», and «Antichamber», the author analyses the constituents of metaphors and defines their functional role as the main stylistic device in the computer discourse.